Flexural performance test and reliability calculation of double reinforced concrete beams with low compression zone height - Liu, Xiang (AIP advances, 2025)
In order to analyze the flexural performance and reliability of reinforced concrete beams with low compression zone height, flexural tests were applied to 11 beams with the same suitable reinforcement whose compression zone height was less than two times the distance between the joint force point of the compressive reinforcement and the compression edge of the section. Results showed that one reinforced concrete beam was loaded to failure and the other 10 were loaded to yield. Through the whole-process analysis of the normal section bending test, it showed that the bending failure of the reinforced concrete beam bore some similarity with the ductile failure of the beam with proper reinforcement. This paper verified the approximate formula for calculating the flexural capacity of reinforced concrete beams (whose compression zone height was less than two times the distance between the resultant point of the compressive reinforcement and the compression edge of the section) and analyzed their deflection and reliability at the normal service stage. Results showed that there was little error between the calculation results and the experimental value; the deflection calculated according to the seismic design codes correlated well with those derived from the test-data-fitted deflection formula; the reliability was lower than the required value in the Unified Standard for Reliability Design of Engineering Structures (GB50153-2008). Therefore, it is suggested to take measures such as enhancing the yield strength of the reinforcement or increasing the reinforcement ratio.